2020
DOI: 10.1590/0037-8682-0177-2020
|View full text |Cite
|
Sign up to set email alerts
|

Triatomine bugs (Hemiptera, Reduviidae, Triatominae) in the Domiciles of the Guaribas Valley Territory, in Northeastern Brazil

Abstract: Introduction: Triatomine bugs are hematophagous insects that are extremely important in public health because they are natural vectors of Trypanosoma cruzi, the causative agent of Chagas disease. In this study, we aimed to assess the occurrence of triatomine species and the natural T. cruzi infection in the Guaribas Valley territory, an endemic region for Chagas disease in northeastern Brazil. Methods: Insects were actively captured from July 2017 to October 2019 in the intra-and peridomiciles of 16 municipali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…We highlight the fact that R. domesticus was registered between 2017 and 2019 in Inhaúma, Itainópolis, and Picos, all municipalities of Piauí (PI) (Mendes-Sousa et al, 2020). An earlier extensive revision work of Chagas disease comprises PI regions in the distribution of R. domesticus (Carcavallo et al, 1999).…”
Section: R Domesticus Occurrence Recordsmentioning
confidence: 79%
See 3 more Smart Citations
“…We highlight the fact that R. domesticus was registered between 2017 and 2019 in Inhaúma, Itainópolis, and Picos, all municipalities of Piauí (PI) (Mendes-Sousa et al, 2020). An earlier extensive revision work of Chagas disease comprises PI regions in the distribution of R. domesticus (Carcavallo et al, 1999).…”
Section: R Domesticus Occurrence Recordsmentioning
confidence: 79%
“…However, searching through the book's referenced literature, we found no mention of the species in the geopolitical area (Lent and Wygodzinsky, 1979;Silveira et al, 1984;Carcavallo and Martínez, 1985;Espinola, 1985). Therefore, the founding of R. domesticus in PI between (Mendes-Sousa et al, 2020 could be the first time the species has been adequately reported in the state.…”
Section: R Domesticus Occurrence Recordsmentioning
confidence: 91%
See 2 more Smart Citations